Artificial turf research at Loughborough University - Fleming, P.; Forrester, S. (Procedia Engineering, 2014)
Research into artificial turf surfaces can be divided into the categories infrastructure, user safety and play performance. This paper discusses these three categories, presents current knowledge and appraises some remaining questions. A simple diagrammatic framework is proposed for describing and relating the fundamental components of sport surface related research. Infrastructure includes the design, construction, operation, and whole life costs associated with a facility. A key area for future research is to better understand maintenance and the benefits of various strategies / techniques. User safety, or injury risk, is a key concern for many stakeholders. Injury risk is a complex interaction of many factors related to the user, sport, equipment and environment. Whilst the introduction of an injury consensus in the late 1990s permitted much greater impact of studies in soccer and rugby, these have contributed little to understanding injury mechanisms. Furthermore, previous research is hampered with regard to the effect of the surface by utilizing simple mechanical tests that appear inappropriate to user activity, e.g. traction. Advancement of knowledge within this category demands better integration with play performance related measurements and research methods that support a more mechanistic approach. Play performance has been the focus of much recent research. For example, mechanical evaluation of surface systems in the laboratory / field, player testing with regard to player and surface response and perception of surface performance. There exists a real need to develop a `consensus` in establishing suitable boundary conditions for both mechanical and player testing. This would help to identify the fundamental research questions related to play performance and allow improved comparison between research studies.